Islamic Religiosity and Pro-Environmental Behavior among Muslim Youth: An Integrative Public Health Approach to Climate Change Mitigation in Indonesia - Nurhayati Nurhayati; Putra Apriadi Siregar; Sri Cahyanti; Nurhayati Saragih; Muhammad Rezebri; Putri Safira; Apriliani Apriliani; Sri Rahayu; Prima Yanti Siregar (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Introduction: The global climate crisis poses an unprecedented threat to human health, yet in highly religious societies such as Indonesia, integrating Islamic values into public health strategies for environmental behavior remains largely unexplored. Objective: This study aims to analyze the relationship between religiousness, pro-environmental attitudes, and environmentally friendly behavior among Muslim adolescents in North Sumatra Province, Indonesia. Methods: A cross-sectional study was conducted with 1,291 students from Islamic universities in Medan, selected through purposive sampling. Data were collected using a validated online questionnaire to measure religiosity, attitudes toward the environment, and self-reported pro-environmental behavior. Because the data distribution was not normal (p < 0.001), Spearman's rank correlation was used to test the hypothesis with JASP version 19 software at a 95% confidence level. Results: A statistically significant positive correlation was found between religiosity and pro-environmental behavior (r = 0.501, p < 0.001). In addition, a stronger positive correlation was observed between religiosity and attitudes toward the environment (r = 0.565, p < 0.001). These results indicate that higher levels of religious commitment are systematically associated with greater ecological awareness and action. Conclusion: Religiosity is a significant determinant of pro-environmental attitudes and behaviors among Muslim youth in Indonesia. Integrating environmental fiqh (Fiqh al-Bi’ah) into public health interventions offers a powerful and culturally rooted strategy for reducing climate-related health risks. Keywords: Islamic, Public Health, Pro-Environmental Behavior, Religiosity.